P2X7 receptor drives Th1 cell differentiation and controls the follicular helper T cell population to protect against Plasmodium chabaudi malaria. - Érika Machado de Salles; Maria Nogueira de Menezes; Renan Siqueira; Henrique Borges da Silva; Eduardo Pinheiro Amaral; Sheyla Inés Castillo-Méndez; Isabela Cunha; Alexandra Dos Anjos Cassado; Flávia Sarmento Vieira; David Nicholas Olivieri; Carlos Eduardo Tadokoro; José Maria Alvarez; et al. (PLoS Pathogens)
A complete understanding of the mechanisms underlying the acquisition of protective immunity is crucial to improve vaccine strategies to eradicate malaria. However, it is still unclear whether recognition of damage signals influences the immune response to Plasmodium infection. Adenosine triphosphate (ATP) accumulates in infected erythrocytes and is released into the extracellular milieu through ion channels in the erythrocyte membrane or upon erythrocyte rupture. The P2X7 receptor senses extracellular ATP and induces CD4 T cell activation and death. Here we show that P2X7 receptor promotes T helper 1 (Th1) cell differentiation to the detriment of follicular T helper (Tfh) cells during blood-stage Plasmodium chabaudi malaria. The P2X7 receptor was activated in CD4 T cells following the rupture of infected erythrocytes and these cells became highly responsive to ATP during acute infection. Moreover, mice lacking the P2X7 receptor had increased susceptibility to infection, which correlated with impaired Th1 cell differentiation. Accordingly, IL-2 and IFNγ secretion, as well as T-bet expression, critically depended on P2X7 signaling in CD4 T cells. Additionally, P2X7 receptor controlled the splenic Tfh cell population in infected mice by promoting apoptotic-like cell death. Finally, the P2X7 receptor was required to generate a balanced Th1/Tfh cell population with an improved ability to transfer parasite protection to CD4-deficient mice. This study provides a new insight into malaria immunology by showing the importance of P2X7 receptor in controlling the fine-tuning between Th1 and Tfh cell differentiation during P. chabaudi infection and thus in disease outcome.